2008
DOI: 10.1074/jbc.m709689200
|View full text |Cite
|
Sign up to set email alerts
|

A Dynamic Polymerase Exchange with Escherichia coli DNA Polymerase IV Replacing DNA Polymerase III on the Sliding Clamp*

Abstract: An assay that measures synchronized, processive DNA replication by Escherichia coli DNA polymerase III holoenzyme was used to reveal replacement of pol III by the specialized lesion bypass DNA polymerase IV when the replicative polymerase is stalled. When idled replication is restarted, a rapid burst of pol III-catalyzed synthesis accompanied by ϳ7-kb full-length products is strongly inhibited by the presence of pol IV. The production of slower-forming, shorter length DNA reflects a rapid takeover of DNA synth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
134
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(139 citation statements)
references
References 32 publications
5
134
0
Order By: Relevance
“…Moreover, it has been shown that replication forks slow down in response to DNA damage, when RecA and TLS Pols are produced (3). In vivo overexpression of Pol IV greatly slows DNA replication (2,15). Additional genetic studies also indicate that Pols II and IV gain access to the replication fork in a RecA-mediated fashion (52).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, it has been shown that replication forks slow down in response to DNA damage, when RecA and TLS Pols are produced (3). In vivo overexpression of Pol IV greatly slows DNA replication (2,15). Additional genetic studies also indicate that Pols II and IV gain access to the replication fork in a RecA-mediated fashion (52).…”
Section: Discussionmentioning
confidence: 99%
“…Both in vivo and in vitro studies indicate that TLS Pols can switch with the Pol III replicase during replication and that the switching process mainly occurs by simple mass action (2,15,17). Although mass action may be an important determinant, most likely the process is more complex (14,38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In bacteria, the homodimeric clamp utilizes twin peptide-binding pockets on the monomer subunits to facilitate dynamic switching between the replicative polymerase and various repair polymerases (26,27). During active DNA synthesis by the replicative polymerase, our model suggests that a repair polymerase bound to the second peptide-binding site on the clamp would be physically blocked from accessing the primer-template junction by the exonuclease domain (Fig.…”
Section: Structural Clues To the Evolution Of The 3 -5 Exonuclease Inmentioning
confidence: 99%
“…Such a mechanism is certainly possible under irradiation of ionizing radiation of DNA molecule. The action of the free radicals, mainly singlet oxygen leads to spontaneous mutagenesis [137,138]. In these cases, as is known, a large number of damages of DNA bases and of sugar-phosphate backbone are formed [137,138].…”
Section: /14mentioning
confidence: 99%